Captured countryside? Stability and change in sub-national support for African incumbent parties - Catherine Boone; Michael Wahman (London School of Economics and Political Science (LSE), Department of International Development, 2015)
Many existing accounts of African elections assume that voters base their electoral decisions on cues and incentives that are anchored in highly stable ethnic cleavage structures. Yet several newer contributions to the study of African electoral politics have questioned the ethno-clientelistic voting thesis and highlighted other determinants of vote choice, such as class, ideology and performance evaluation. Existing research has, however, not dealt with geographic dimensions of electoral dynamics. In this paper we contribute to this literature by studying Government-Opposition Swing (GOS) voting in 7 African countries, 28 elections and 1900 parliamentary constituencies. We show that the likelihood of GOS differs from urban to rural, and across different types of rural constituencies. GOS is significantly more common in urban areas and in highly populated rural areas, but significantly less common in the president's home region and in sparsely populated rural regions. The results suggest that electoral and voting dynamics vary across space, even within a single country. We draw inferences about how political and economic geography shapes prospects for autonomous vote choice and performance-related voting.
Keywords: 330; Political Order; Security and Justice; Conflict States; Dualism; Hybrid Institutions; Malinowski